Summary of Readings in Neurosurgery. - Abdullah, Jafri Malin; Jafri Malin Abdullah; Jahaya, Noriyanti; Jaapar, Mohammad Ridhwan; Rahim, Norjannah Abdul; ProQuest (Firm) (Pulau Pinang : Penerbit USM, 2013)
If you are looking for a straightforward and readable summary of neurosurgical cases, this book is the best for you. This book can provide you with convenient means of reference especially for medical practitioners, and can be a good guide for everyone that has interest in the neurosurgery field. Summary of Readings in Neurosurgery: Brain is the book for readers who needs to know about neurosugery for brain. It is presented in clear, subject by subject briefings with examples and pictures to illustrate the application of the neurosurgery and to help readers understand various topics and cases r.
Giant Clival Chordoma -- Facial Degloving TechniqueSuprasella Chondroma; Pediatric Supratentorial Extraventricular Ependymoma; Endoscopic Pituitary Surgery for Sellar Region Tumor; Giant Pituitary Adenoma; Pineal Region Tumor; Anterior Third Ventricular Tumor -- Transcallosal Approach; Oligodendroglioma Treated with Radiosurgery Under General Anesthesia; Thalamic Tumor; Supratentorial Cerebral Metastases; Supratentorial Primitive Neuroectodermal Tumors; Cerebellar Pilocytic Astrocytoma; Contributors; Index.
Description based upon print version of record.
Print version record.
eBooks on EBSCOhost
Keywords: Nervous system -- Surgery; Brain -- Surgery; Nervous system; Brain -- surgery; Nervous System; Neurosurgical Procedures; Neurosurgery; Neurochirurgie; Cerveau -- Chirurgie; Système nerveux; Nervous system; Brain -- Surgery; Nervous system -- Surgery